Approximate Word-Lattice Indexing with Text Indexers: Time-Anchored Lattice Expansion - Yu, Peng; Shi, Yu; Seide, Frank; Yu, Roger (Peng) (Proc. IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2008)
We address the problem of how to represent or approximate speech lattices to be indexed with existing text indexers. We present a method named time-anchored lattice expansion (TALE), which can be implemented by a standard text indexer (STI). On a 170- hour lecture set, we compare TALE with other lattice indexing methods: confusion networks, position-specific posterior lattices (PSPL), and time-based merging for index (TMI). All methods achieve accuracies comparable to searching raw lattices when the corresponding index structures and phrase matching algorithms are used. However, when implemented with an STI, TALE significantly outperforms all other methods. Compared to indexing linear text, TALE improves accuracy by 30-60% for multi-word phrase searches and by 130% for two-term AND queries.